Microstructure and properties of joint of Al/Cu welded by resistance element welding with an auxiliary gasket of Ni - Dongsheng Cui; Jing Wang; Ranfeng Qiu; Hongxin Shi; Lipeng Yan (Scientific Reports)
Abstract A rivet of aluminum and auxiliary gasket of nickel were adopted to weld A1060 aluminum plate and T2 copper plate using resistance element welding. The interfacial microstructure was analyzed and the tensile shear load of the joint was tested. A layer of Al2Cu and the eutectic structure of Al2Cu and (Al) were formed in the interfacial zone of Al/Cu. The grains in Al2Cu layer exhibit random crystal orientations. With the increase of welding current and the extension of welding time, the tensile shear load of the Al/Cu joint increased first and then decreased. When the welding current was 30 kA, the welding time was 400 ms, the tensile shear load of the joint reached the maximum, approximately 2.55 kN. The results reveal that the application of nickel auxiliary gasket in the resistance element welding of Al/Cu can promote the joining between the rivet shank and the upper plate and increase the tensile shear load of the joint.